2016
DOI: 10.1111/jog.12959
|View full text |Cite
|
Sign up to set email alerts
|

Occult fetomaternal hemorrhage in women with pathological placenta with respect to permeability

Abstract: Aim: Women with preeclampsia, placenta previa (PP), placental abruption (PA), and placental mesenchymal dysplasia (PMD) were suggested to have placental permeability dysfunction. This study was performed to determine whether occult fetomaternal hemorrhage (FMH) is common in women with such complications and in women with non-reassuring fetal status (NRFS).Methods: Forty-one antenatal and 39 postnatal blood samples were obtained from 46 women consisting of 11 with complications (5, 3, 2, and 1 with preeclampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…And the prospective risk of stillbirth with PMD was significantly high at any GW of 24 or later with median GW of 31 . In addition, as one of the specific causes of IUFD with PMD, fetomaternal hemorrhage is suggested . And, four IUFD/stillbirth cases out of 27 PMD cases (14.8%) seemed consistent with the rate as the complication of PMD based on previous studies .…”
Section: Discussionsupporting
confidence: 81%
“…And the prospective risk of stillbirth with PMD was significantly high at any GW of 24 or later with median GW of 31 . In addition, as one of the specific causes of IUFD with PMD, fetomaternal hemorrhage is suggested . And, four IUFD/stillbirth cases out of 27 PMD cases (14.8%) seemed consistent with the rate as the complication of PMD based on previous studies .…”
Section: Discussionsupporting
confidence: 81%
“…Pre‐eclampsia, stillbirth, fetal growth restriction and preterm birth are currently considered as placenta‐mediated disorders . A number of studies revealed that placental barrier dysfunction might occur in these disorders . Furthermore, it was found in animal studies that LPS could compromise placental barrier integrity and affect its permeability .…”
Section: Discussionmentioning
confidence: 99%
“…9,21 A number of studies revealed that placental barrier dysfunction might occur in these disorders. [22][23][24] Furthermore, it was found in animal studies that LPS could compromise placental barrier integrity and affect its permeability. 25,26 It was also observed in the in vitro study that inflammatory cytokines could weaken the placental barrier through destruction of tight junctions at trophoblastic and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth, preeclampsia and SGA are currently considered as "placenta-mediated" disorders [28][29][30]. A series of evidences indicated that increased placental permeability might occur in these disorders [31][32][33]. Therefore, we may infer that, starting from the end of the first trimester when the primitive placenta undergoes remodeling to form the definitive organ [34], the increase in placental permeability is a gradually developed process under certain pathological conditions.…”
Section: Discussionmentioning
confidence: 99%